Production of Restorer Lines from Segregating Progenies of Brassica napus L. Having Good Agronomic Value - Islam, A. K. M. Aminul; Era, F. M.; Chowdhury, N. K. Aminul (International Journal of Applied Sciences and Biotechnology, 2020)
Forty four testcross progenies obtained from crossing between five CMS and forty one candidate lines were evaluated both in field and laboratory condition to identify candidate restorer line(s). Nineteen testcross progenies were recorded as fully fertile with 100% plant fertility by counting the number of fertile plants from the total number of plants per lines. On the other hand from pollen fertility test, 11 testcross progenies [206A × 001(6), 9905A × 030(2), 9905A × 027(6) (0.57), 206A × 37(1) (0.68), 9904A × 027(4) (0.83), 248A × 020(6) (1.08), 248A × 018 (1.12), 248A × 022 (1.13), 248A × 017 (1.58), 248A × 038(2) (1.96) and 248A × 001(6) (2.02)] were found with 0-2.02% pollen sterility that could be mentioned as fertile or restorer lines for making hybrids. Agronomic performances were also satisfactory for these selected test cross progenies. The genotype 248A × 017 took the shortest time (30.00) for first flowering as well as ripening followed by 248A × 007(1). The highest number of pods per plant was observed in the testcross progeny 248A × 022 (649.59) and the highest number of seeds per pod (30.33) in 248A × 020(6). For seed weight per plant, 206A × 001(6) was recorded with maximum value (0.08g) while the lowest (23.33) number of seeds per plant was found in this progeny. In case of seed yield per plant, 248A × 022 gave the highest yield (30.30). The seed yield of the progenies 248A × 017 (23.49), 9905A × 027(6) (20.39), 248A × 001(6) (17.26), 9904A × 027(4) (17.02) and 248A × 038(2) (16.53) were also in the highest level.